Seeing is Believing : Poverty in the Palestinian Territories - World Bank (Washington, DC, 2014)
The Palestinian Territories have a uniquely fragmented geography, characterized by the isolation of Gaza from the rest of the world, and the man-made barriers to mobility within the West Bank. The internal mobility restrictions imposed by Israel, unique to the West Bank, play an important role in explaining spatial variations in outcomes within the West Bank. This is strikingly analogous to the role of Gaza's external barriers in explaining the divergence between the West Bank and Gaza. These have consequences for poverty and economic development. Detailed analysis using a series of labor force and household surveys were undertaken as part of the West Bank and Gaza poverty and inclusion assessment, coping with conflict? The analysis revealed that over the last decade, internal and external barriers have been associated with tremendous constraints to growth and investment, which is evident in high rates of unemployment, especially in Gaza and among women and youth. Poverty mapping relies on household survey and census data, making the most of the strengths of each, and compensating for their weaknesses. Certain key data requirements must be fulfilled to be able to construct a poverty map. Survey data must include detailed consumption data, which is the basis for calculating poverty estimates, for instance at the national and the regional level. However, the survey usually covers only a representative sample of the population. This tradeoff between sample size and the cost and time needed to collect quality consumption data implies that surveys cannot typically be used to calculate reliable poverty estimates for more disaggregated areas. This is because, at such lower levels of disaggregation, for instance, the community or village, the number of observations in the survey is too small to produce statistically reliable estimates. The census on the other hand covers the entire population and can therefore be reliable even at lower levels of aggregation. However, the census usually covers only basic information like demographics, education and employment but not detailed information on consumption.